Body distribution of Bothrops asper (terciopelo) snake venom myotoxin and its relationship to pathological changes - Moreno Robles, Edgardo (1988)
The distribution of 125I-labelled Bothrops asper myotoxin following i.m. and i.v. injections was studied in mice. After i.m. administration the toxin was concentrated in the injected gastrocnemius muscle, with relatively little binding to other tissues. Upon i.v. injection the highest radioactivity was detected in liver, kidneys, lungs, spleen and blood. A conspicuous decrease in myotoxin concentration occurred during the first hour, whereas the rate of decrease was reduced at later time periods. Only the injected skeletal muscle was clearly damaged after i.m. inoculation, as judged by histology and by the decrease in tissue creatine kinase contents. Contralateral, noninjected gastrocnemius was not affected by the toxin. Histological observations carried out after i.v. administration of the toxin revealed moderate alterations only in lungs, with a slight increase in serum levels of the enzymes creatine kinase and alanine aminotransferase.